Hard carbon negative electrode material and preparation method and application thereof
By mixing coal-based materials with aliphatic compounds containing S and/or N, spray granulation and high-temperature carbonization, a hard carbon negative electrode material with a larger interlayer spacing and rich closed pore structure was prepared, which solved the irreversible reaction and cycle stability problems of hard carbon materials in sodium ion batteries, and achieved higher rate performance and cycle stability.
Patent Information
- Application Number
- CN202510121926.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-01-26
AI Technical Summary
Hard carbon materials have a large specific surface area and a large number of defects in sodium ion batteries, resulting in an increase in irreversible reactions, a decrease in the first charge and discharge efficiency, and insufficient rate performance and cycle stability.
By mixing the coal-based material with aliphatic compounds containing S and/or N, spray granulation and pre-oxidation treatment, and finally carbonizing under an inert atmosphere, a hard carbon negative electrode material with a larger interlayer spacing and rich closed pore structure was prepared.
It improves the reversible capacity, first-time efficiency and cycle life of hard carbon negative electrode materials, enhances the rate performance and cycle stability of sodium ion batteries, and simplifies the process and facilitates industrial promotion.
Smart Images

Figure CN119660715A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ion batteries, and in particular relates to a hard carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] Among the many negative electrode materials for sodium-ion batteries, carbon-based materials have developed the fastest due to their wide sources, significant cost and commercial production advantages. Among them, hard carbon negative electrodes with high disorder and large interlayer spacing have higher storage capacity, lower operating voltage and excellent cycle stability. Common hard carbons include resin-based, coal-based materials and biomass hard carbon.
[0003] However, hard carbon has a large specific surface area and a large number of defects, and a large number of irreversible reactions will occur during the first charge and discharge process, resulting in a decrease in the initial efficiency of the battery. The internal kinetic properties, including the conductivity of electrons and the diffusion rate of ions, are poor, resulting in poor rate performance of the material. In addition, during the charge and discharge process, the structure of hard carbon may be destroyed, thereby affecting its cycle stability. These shortcomings of hard carbon materials need to be solved through material modification and structural design optimization to improve the performance and stability of sodium-ion batteries.
[0004] Therefore, optimizing hard carbon materials to make them more suitable for nano-ion batteries has received increasing attention. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, an embodiment of the present invention provides a method for preparing a hard carbon negative electrode material, wherein the hard carbon material prepared by the method has a larger interlayer spacing (0.399nm) and a rich closed pore structure, which is beneficial to ion diffusion kinetics and improves the gram capacity, first efficiency and cycle life of the hard carbon negative electrode material.
[0006] The method for preparing the hard carbon negative electrode material according to the embodiment of the present invention comprises the following steps:
[0007] (1) subjecting the coal-based material to ball milling and impurity removal treatment to obtain a coal-based nanomaterial;
[0008] (2) mixing the coal-based nanomaterial obtained in step (1) with an aliphatic compound containing S and / or N, and spray granulating the mixture to obtain a mixed material;
[0009] (3) The mixed material obtained in step (2) is first subjected to a pre-oxidation treatment, and then subjected to a carbonization treatment under an inert atmosphere to obtain a hard carbon negative electrode material.
[0010] The advantages and technical effects brought by the preparation method of the hard carbon negative electrode material of the embodiment of the present invention are as follows: 1. The method of the embodiment of the present invention mixes the coal-based material and the aliphatic compound and obtains a polymer network composite precursor through spray granulation and pre-oxidation treatment. The composite precursor can inhibit graphitization during the high-temperature carbonization process, so that the hard carbon material has a larger interlayer spacing (0.399nm) and a rich closed pore structure, which is beneficial to the ion diffusion kinetics and improves the gram capacity, initial efficiency and cycle life of the hard carbon negative electrode material; 2. The method of the embodiment of the present invention selects an aliphatic compound containing S and / or N; wherein the aliphatic compound containing N The compound can make the polymer network composite precursor obtained by pre-oxidation treatment produce CN free radicals during the carbonization process, and then construct a hard carbon material with rich defects and enlarged interlayer spacing, which can greatly improve the rate performance and cycle stability of sodium ion batteries; the aliphatic S-containing compound can provide more active sites for the storage of sodium ions in the hard carbon layer, so that the hard carbon material can exhibit a larger reversible capacity, excellent cycle performance and better cycle stability, and there is no vacancy defect; 3. The method of the embodiment of the present invention has a simple process, and the prepared hard carbon negative electrode material has good comprehensive performance, which is convenient for promotion and application in industrial production.
[0011] In some embodiments, in step (1), the solution used for the impurity removal treatment includes at least one of HF solution and / or HCl solution.
[0012] In some embodiments, in step (2), the mass ratio of the coal-based nanomaterial to the aliphatic compound is (5-15):1.
[0013] In some embodiments, in step (2), the particle size of the mixed material obtained after the spray granulation is 5 to 12 μm.
[0014] In some embodiments, in step (3), the temperature of the pre-oxidation treatment is 200 to 400° C., and the time of the pre-oxidation treatment is 1 to 3 hours.
[0015] In some embodiments, in step (3), the temperature of the carbonization treatment is 1000-1600° C., and the time of the carbonization treatment is 2-4 hours;
[0016] And / or, the temperature of the pre-oxidation treatment is increased to the temperature of the carbonization treatment at a heating rate of 1 to 5° C. / min.
[0017] In some embodiments, in step (3), the inert atmosphere includes at least one of argon or nitrogen.
[0018] The embodiment of the present invention further provides a hard carbon negative electrode material, which is prepared by the above-mentioned preparation method.
[0019] The embodiment of the present invention further provides a negative electrode plate, comprising the hard carbon negative electrode material prepared by the above preparation method or the above hard carbon negative electrode material.
[0020] An embodiment of the present invention further provides a sodium ion battery, comprising the above-mentioned negative electrode plate. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the charge and discharge curve of the battery prepared in Example 1 in the first week. DETAILED DESCRIPTION
[0022] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0023] The method for preparing the hard carbon negative electrode material according to the embodiment of the present invention comprises the following steps:
[0024] (1) subjecting the coal-based material to ball milling and impurity removal treatment to obtain a coal-based nanomaterial;
[0025] (2) mixing the coal-based nanomaterial obtained in step (1) with an aliphatic compound containing S and / or N, and spray granulating the mixture to obtain a mixed material;
[0026] (3) The mixed material obtained in step (2) is first subjected to a pre-oxidation treatment, and then subjected to a carbonization treatment under an inert atmosphere to obtain a hard carbon negative electrode material.
[0027] The preparation method of the hard carbon negative electrode material of the embodiment of the present invention is to mix the coal-based material and the aliphatic compound and obtain a polymer network composite precursor through spray granulation and pre-oxidation treatment. The composite precursor can inhibit graphitization during the high-temperature carbonization process, so that the hard carbon material has a larger interlayer spacing (0.399nm) and a rich closed pore structure, which is beneficial to the ion diffusion kinetics and improves the gram capacity, initial efficiency and cycle life of the hard carbon negative electrode material; the method of the embodiment of the present invention selects an aliphatic compound containing S and / or N; wherein the aliphatic N-containing compound can make the polymer network composite precursor obtained by the pre-oxidation treatment produce CN free radicals during the carbonization process, and then a hard carbon material with rich defects and enlarged interlayer spacing can be constructed, which can greatly improve the rate performance and cycle stability of the sodium ion battery; the aliphatic S-containing compound can provide more active sites for the storage of sodium ions in the hard carbon layer, so that the hard carbon material can show a larger reversible capacity, excellent cycle performance and better cycle stability, and there is no vacancy defect; the method of the embodiment of the present invention is simple in process, and the prepared hard carbon negative electrode material has good comprehensive performance, which is convenient for promotion and application in industrial production.
[0028] In some embodiments, preferably, in the step (1), the solution used for the impurity removal treatment includes at least one of HF solution and / or HCl solution.
[0029] In some embodiments, preferably, in step (2), the aliphatic compound containing S and / or N includes thiourea (CH4N2S), cysteine (C3H7NO2S), penicillamine (C5H 11 NO2S), at least one of aminothiol compounds or aminothiophenol compounds.
[0030] In some embodiments, preferably, in the step (2), the mass ratio of the coal-based nanomaterial and the aliphatic compound is (5-15):1, for example, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, etc.
[0031] In the embodiment of the present invention, the mass ratio of aliphatic compounds and coal-based nanomaterials is optimized, which is conducive to obtaining negative electrode materials with good comprehensive performance; if the amount of aliphatic compounds is too low, the active sites of the hard carbon material obtained are insufficient, the interlayer spacing is reduced, and the rate performance and cycle performance of the battery are reduced; if the amount of aliphatic compounds is too high, the conductivity of the hard carbon material obtained is reduced, the resistance of the negative electrode film obtained subsequently is increased, and the cycle performance of the battery cell is reduced.
[0032] In some embodiments, preferably, the particle size of the mixed material obtained after the spray granulation is 5 to 12 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, etc.
[0033] In some embodiments, preferably, in the step (3), the temperature of the pre-oxidation treatment is 200-400°C, for example, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, etc.; the time of the pre-oxidation treatment is 1-3h, for example, 1h, 1.5h, 2h, 2.5h, 3h, etc.
[0034] In some embodiments, preferably, in step (3), the temperature of the carbonization treatment is 1000-1600°C, such as 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, etc.; the time of the carbonization treatment is 2-4h, such as 2h, 2.5h, 3h, 3.5h, 4h, etc.;
[0035] And / or, the temperature of the pre-oxidation treatment is increased to the temperature of the carbonization treatment at a heating rate of 1 to 5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, etc.
[0036] In some embodiments, preferably, in step (3), the inert atmosphere includes at least one of argon or nitrogen.
[0037] The embodiment of the present invention further provides a hard carbon negative electrode material, which is prepared by the above-mentioned preparation method.
[0038] The embodiment of the present invention further provides a negative electrode plate, comprising the hard carbon negative electrode material prepared by the above preparation method or the above hard carbon negative electrode material.
[0039] An embodiment of the present invention further provides a sodium ion battery, comprising the above-mentioned negative electrode plate.
[0040] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and drawings.
[0041] Example 1
[0042] (1) Weighing a certain mass of coal-based material, with the mass ratio of coal-based material to ball milling beads being 1:20; ball milling the material in a ball mill at a speed of 1200 rpm for 4 h, taking out the milled material, washing it with 1 M HCl, and drying it to obtain the coal-based nanomaterial;
[0043] (2) adding coal-based nanomaterials and thiourea (CH4N2S) in a mass ratio of 10:1 into a solvent ethanol and mixing them evenly, and spray granulating them to obtain a mixed material with a particle size of 8 μm;
[0044] (3) placing the mixed material in a muffle furnace and pre-oxidizing and heat treating it at 300°C in air for 1 hour to obtain a polymer network composite precursor; raising the temperature to 1400°C at a heating rate of 2°C / min, and then keeping the polymer network composite precursor at 1400°C for 2 hours under an inert atmosphere of argon to obtain a hard carbon negative electrode material HC-1400 after high temperature carbonization;
[0045] (4) HC-1400 was homogenized with Super P, CMC, and SBR in a mass ratio of 94:1:1.8:3.2, and an appropriate amount of deionized water was added during the homogenization. The uniformly mixed slurry was then coated on an aluminum foil current collector substrate to obtain a negative electrode sheet; and then a CR2032 button half-cell was formed with a sodium sheet, and the electrolyte used was NaClO4 (EC+DEC+5%FEC).
[0046] Example 2
[0047] The preparation method of this embodiment is the same as that of embodiment 1, except that the high-temperature carbonization temperature in step (3) is 1200°C.
[0048] Example 3
[0049] The preparation method of this embodiment is the same as that of embodiment 1, except that the high-temperature carbonization temperature in step (3) is 1600°C.
[0050] Example 4
[0051] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (2), the mass ratio of the coal-based nanomaterial to the aliphatic compound is 5:1.
[0052] Example 5
[0053] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (2), the mass ratio of the coal-based nanomaterial to the aliphatic compound is 15:1.
[0054] Comparative Example 1
[0055] (1) Weighing a certain mass of coal-based material, with the mass ratio of coal-based material to ball milling beads being 1:20; ball milling the material in a ball mill at a speed of 1200 rpm for 4 h, taking out the milled material, washing it with 1 M HCl, and drying it to obtain the coal-based nanomaterial;
[0056] (2) adding the coal-based nanomaterials into the solvent ethanol and mixing them evenly, and spray granulating them to obtain a mixed material;
[0057] (3) placing the mixed material in a muffle furnace for pre-oxidation heat treatment at 300°C in air for 1 h, and then keeping the temperature at 1400°C for 2 h in an inert atmosphere of argon to obtain a hard carbon negative electrode material HC-C after high-temperature carbonization;
[0058] (4) The battery assembly is the same as in Example 1.
[0059] The performance test of the batteries prepared in Examples 1 to 5 and Comparative Example 1 is shown in Table 1. The first week charge and discharge curve of the battery prepared in Example 1 is as follows: Figure 1 shown.
[0060] Table 1
[0061] First effect (%) Capacity (mAh / g) Capacity retention after 50 cycles at 1C (%) Example 1 91.6 311.1 97.5 Example 2 87.3 310.5 95.9 Example 3 91.2 299.7 95.3 Example 4 90.1 294.1 97.0 Example 5 87.8 270.5 96.6 Comparative Example 1 84.2 260.2 97.2
[0062] The sodium ion battery prepared in the embodiment of the present invention has a high first efficiency, capacity and excellent capacity retention rate. It can be seen from the data of Examples 1 to 3 that with the increase of carbonization temperature, the first efficiency and capacity of the battery both show a trend of first increasing and then decreasing. This is because the hard carbon material obtained by carbonization at a lower temperature has more heteroatoms and a large number of defects. High-energy defects are adsorbed to form dead sodium and react with the electrolyte to form an SEI film. Therefore, the first coulomb efficiency is low when carbonized at a lower temperature; with the increase of carbonization temperature, the specific surface area of the hard carbon material decreases, the pore size increases, and the high-temperature treatment causes the graphite microcrystals to undergo structural transformation. In this process, a large amount of deoxygenation and denitrification occurs, the degree of graphitization increases, the specific surface area of the hard carbon decreases sharply, and some poorly stacked amorphous carbon changes toward order, which causes some micropores to collapse and disappear, and some micropores grow to form mesopores, resulting in a decrease in capacity.
[0063] In Example 4 and the examples, the mass ratio of the coal-based material to the aliphatic compound was adjusted. The amount of the aliphatic compound in Example 4 was more than that in Example 1, and the first effect remained basically unchanged, but the capacity was reduced. Adding too many aliphatic compounds would occupy the active sites in the hard carbon material, so the first effect remained basically unchanged and the capacity was reduced. The amount of the aliphatic compound in Example 5 was less than that in Example 1, and the N / S element content in the generated hard carbon material was low, which reduced the first effect and capacity of the prepared hard carbon material, and the capacity retention rate decreased.
[0064] In Comparative Example 1, only coal-based materials were used to prepare hard carbon materials. Not only was the first efficiency able to be maintained at 84.2%, but the capacity was also reduced to 260.2 mAh / g.
[0065] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0066] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A method for preparing a hard carbon negative electrode material, characterized in that: The following steps are involved: (1) subjecting the coal-based material to ball milling and impurity removal treatment to obtain a coal-based nanomaterial; (2) mixing the coal-based nanomaterial obtained in step (1) with an aliphatic compound containing S and / or N, and spray granulating the mixture to obtain a mixed material; (3) The mixed material obtained in step (2) is first subjected to a pre-oxidation treatment, and then subjected to a carbonization treatment under an inert atmosphere to obtain a hard carbon negative electrode material.
2. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: In the step (1), the solution used for the impurity removal treatment includes at least one of HF solution and / or HCl solution.
3. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: In the step (2), the mass ratio of the coal-based nanomaterial to the aliphatic compound is (5-15):
1.
4. The method for preparing a hard carbon negative electrode material according to any one of claims 1 to 3, characterized in that: In the step (2), the particle size of the mixed material obtained after the spray granulation is 5 to 12 μm.
5. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: In the step (3), the temperature of the pre-oxidation treatment is 200 to 400° C., and the time of the pre-oxidation treatment is 1 to 3 hours.
6. The method for preparing a hard carbon negative electrode material according to claim 1 or 5, characterized in that: In the step (3), the temperature of the carbonization treatment is 1000-1600° C., and the time of the carbonization treatment is 2-4 hours; And / or, the temperature of the pre-oxidation treatment is increased to the temperature of the carbonization treatment at a heating rate of 1 to 5° C. / min.
7. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: In the step (3), the inert atmosphere includes at least one of argon or nitrogen.
8. A hard carbon negative electrode material, characterized in that: The method is prepared according to any one of claims 1 to 7.
9. A negative electrode plate, characterized in that: The invention comprises a hard carbon negative electrode material prepared by the preparation method described in any one of claims 1 to 7 or a hard carbon negative electrode material described in claim 8.
10. A sodium ion battery, characterized in that: Including the negative electrode sheet as described in claim 9.
Citation Information
Patent Citations
Biomass hard carbon negative electrode material of sodium ion battery and preparation method of biomass hard carbon negative electrode material
CN113206246A
Preparation method of hard carbon material of nitrogen-oxygen double-doping process modified semi-coke system
CN115124021A
Asphalt-based nitrogen-sulfur double-doped carbon material and application thereof in sodium-ion battery negative electrode material
CN116462182A
Nitrogen-doped carbon material, preparation method and application thereof, adsorption material and application thereof
CN116550285A
Nitrogen, phosphorus and sulfur three-element doped hard carbon material, preparation method and application
CN118306969A